Utility of the 2006 Sendai and 2012 Fukuoka guidelines for the management of intraductal papillary mucinous neoplasm of the pancreas: A single-center experience with 138 surgically treated patients. Issue 38 (September 2016) - Hsiao, Chih-Yang; Yang, Ching-Yao; Wu, Jin-Ming; Kuo, Ting-Chun; Tien, Yu-Wen
Abstract : Abstract: This study aimed to evaluate the utility of the 2006 Sendai and 2012 Fukuoka guidelines for differentiating malignant intraductal papillary mucinous neoplasm (IPMN) of the pancreas from benign IPMN. Between January 2000 and March 2015, a total of 138 patients underwent surgery and had a pathologically confirmed pancreatic IPMN. Clinicopathological parameters were reviewed, and all patients were classified according to both the 2006 Sendai and 2012 Fukuoka guidelines. Univariate and multivariate analyses were used for identifying significant factors associated with malignancy in IPMN. There were 9 high-grade dysplasia (HGD) and 37 invasive cancers (ICs) in the 138 patients. The positive predictive value (PPV) and negative predictive value (NPV) of the Sendai and Fukuoka guidelines for HGD/IC was 35.1%, 43.3%, 100%, and 85.4%, respectively. Of the 36 patients with worrisome features using the Fukuoka guideline, 7 patients had HGD/IC in their IPMNs. According to the multivariate analysis, jaundice, tumors of ≥3 cm, presence of mural nodule on imaging, and aged <65 years were associated with HGD/IC in patients with IPMN. The Sendai guideline had a better NPV, but the Fukuoka guideline had a better PPV. We suggest that patients with worrisome features based on the Fukuoka guideline be aggressively managed.